Antiviral treatment in patients with hepatitis C virus-related cirrhosis awaiting liver transplantation - Pierluigi Toniutto; Carlo Fabris; Davide Bitetto; Ezio Fornasiere; Elisa Fumolo; et al (Dove Medical Press, 2008)
Pierluigi Toniutto1, Carlo Fabris1, Davide Bitetto1, Ezio Fornasiere1, Elisa Fumolo1, Rachele Rapetti2, Mario Pirisi21Medical Liver Transplant Unit, DPMSC, Internal Medicine, University of Udine, Italy; 2Department of Clinical and Experimental Medicine (DiMeCS), University of Eastern Piedmont Amedeo Avogadro, Novara, ItalyAbstract: End stage liver disease due to hepatitis C virus (HCV) infection is the most common indication for liver transplantation (LT) worldwide. Regretfully, infection of the graft by HCV occurs almost universally after LT, causing chronic hepatitis and early progression to cirrhosis in a significant proportion of recipients. Moreover, graft and patient survival are significantly worse in patients undergoing LT for HCV-related cirrhosis than in those transplanted for other indications. Therefore, many LT centers consider antiviral treatment with interferon and ribavirin the mainstay of managing recurrent HCV disease in LT recipients. The optimal time to start treatment is unclear. In most instances, treatment is initiated when histological evidence of disease recurrence, either at protocol or on-demand liver biopsies, is observed after LT. However, antiviral treatment initiated before LT is a potential option for some patients for two reasons: first, clearing or suppressing HCV before LT may reduce or eliminate the risk of recurrent hepatitis C in the transplanted liver and thereby improve survival; second, clearing HCV in cirrhotic patient may halt disease progression and avoid the need for transplantation. In this article, the results obtained by pre-transplant antiviral regimens administered to HCV-positive cirrhotic patients awaiting LT are discussed.Keywords: hepatitis C, antiviral therapy, liver cirrhosis, liver transplantation